Baby animals! - Thomson, Ruth frey50; Fry, Ian Ill. (Gareth Stevens Publishing Milwaukee, 1985)
Introduces baby animals of Africa, the polar ice caps, and North America. Suggests activities for readers to find out more about non-domestic animals.
Includes index
Keywords: Animals -- Infancy -- Juvenile literature